Synthesis of Pb(II) Imprinted Carboxymethyl Chitosan and the Application as Sorbent for Pb(II) Ion - Abu Masykur; Sri Juari Santosa; Dwi Siswanta; Jumina Jumina (Universitas Gadjah Mada, 2014)
The aims of this research is to synthesize Pb(II) imprinted polymers with carboxymethyl chitosan (CMC) as polymers and bisphenol A diglycidyl ether (BADGE) as cross-linker (Pb-IIP). Chitosan (CTS), non imprinted polymer (NIP) and Pb-IIP were characterized using infrared (IR) spectroscopy, X-ray diffraction (XRD), surface area analyzer (SAA), scanning electron microscopy (SEM), and energy dispersive X-ray (EDX) spectroscopy. The result showed that the adsorption was optimum at pH 5 and contact time of 250 min. Adsorption of Pb(II) ion with all of adsorbents followed pseudo-second order kinetic equation. Adsorption of Pb(II) ion on CTS followed Freundlich isotherm while that on NIP and Pb-IIP followed the Langmuir adsorption isotherm. The adsorbent of Pb-IIP give higher capacity than the NIP and CTS. Adsorption capacity of Pb-IIP, NIP and CTS were 167.1, 128.9 and 76.1 mg/g, respectively. NIP gave higher adsorption selectivity for Pb(II)/Ni(II) and Pb(II)/Cu(II), whereas Pb-IIP showed higher adsorption selectivity for Pb(II)/Cd(II).The hydrogen bonding dominated interaction between Pb(II) ion on NIP and Pb-IIP.